Penguatan Pos Upaya Kesehatan Kerja sebagai Literasi K3 pada Sektor Perkebunan di PTPN XII Kota Blater - Sujoso, Anita Dewi Prahastuti; Antika, Ruli Bahyu; Atmawati, Wiwin Dwiana; Syarifuddin, Yusron (UPT Penerbitan Universitas Jember, 2023)
Background: The plantation sector has various kinds of hazards that exist in the environment ranging from physical, chemical, biological, ergonomic, to psychological hazards. This activity aims to provide strengthening for the Occupational Health Effort Post at PTPN XII Kotta Blater, new knowledge related to work risks in plantations and nutrition for plantation workers, as well as health checks for workers; Method: The method of activity is counseling and medical examination which was attended by 52 workers at PTPN XII Kotta Blater; Results: The results showed that the majority of workers had pre-hypertensive blood pressure, BMI obesity level I, high cholesterol levels, normal blood sugar levels, normal uric acid levels, and showed health complaints. The impact of this activity is that workers can understand the risks of work in the working area of rubber plantations and the nutrition of plantation workers and know the diseases that are being suffered; and Conclusion: This activity went quite smoothly but there were still obstacles in terms of officers, readiness of inspection equipment, and technical implementation of activities.Keywords: socialization, plantations, occupational health effort post